꾸지뽕나무 잎과 우슬 복합물이 MIA로 골관절염이 유도된 Rat에 미치는 영향 - 정길호(Kil-Ho Cheong); 주인환(In-Hwan Joo); 김동희(Dong-Hee Kim) (동의생리병리학회지, 2023)
This study was to investigate the effects of cudrania tricuspidata leaf and achyranthes japonica nakai complex (CAC) treatment on monosodium iodoacetate (MIA)-induced osteoarthritis rats. Osteoarthritis was induced by injection of MIA (3 mg) into right knee joints of rats. The rats were divided into 5 groups; Non-induced normal rat (Con, n=10), MIA-induced osteoarthritis rat (MIA, n=10), osteoarthritis rat treated with indomethacin 2 mg/kg (Indo, n=10), osteoarthritis rat treated with CAC 200 mg/kg (Low, n=10) or 400 mg/kg (High, n=10). The rats were treated orally for 14 days. On the last day of oral administration, the hind paw weight bearing of the experimental animals was measured using an incapacitance test meter. The interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), prostaglandin E2 (PGE2), cartilage oligomeric matrix protein (COMP) and, C-telopeptides of type II collagen (CTX-II) levels in serum were measured by ELISA. And Then, that gene expression (IL-1β, IL-6, TNF-α, COX-2) levels in cartilage were measured by qRT-PCR. Also, cartilage volume was measured by micro CT arthrography. Administration of CAC reduced the inflammatory cytokine (IL-1β, IL-6, TNF-α, PGE2) levels in serum and gene expression levels in cartilage, and the COMP and CTX-II level in serum, which is an indicator of cartilage degradation. In addition, the hind paw weight bearing and cartilage volume, which were decreased due to osteoarthritis, were significantly increased. In the future, if the results of clinical studies including studies on safety are supplemented, it is considered that it can be used as an oriental medicine treatment to improve or treat symptoms of osteoarthritis.